Temporal trends in goals scored per match across European soccer leagues: a three-decade analysis - Almeida, C. H. (Trends in Sport Sciences, 2024)
Introduction: Research in soccer has shown that regulatory changes, alongside other factors, shape how the game is played and affect one of its key outcomes-goals scored per match. However, limited data exists on how this trend has evolved in Europe`s major domestic leagues.